2006
DOI: 10.1590/s0037-86822006000200008
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Candida species obtained from nosocomial candidemia using RAPD-PCR technique

Abstract: Thirteen strains of the genus Candida were isolated from catheter, urine and surgical wounds from individual patients of the Santa Casa de Misericórdia, Belo Horizonte, MG, Brazil. Ten strains were characterized as Candida albicans, two as Candida glabrata, and one as Candida parapsilosis. Isolates were evaluated for molecular relatedness by random amplified polymorphic DNA technique using 15 primers. The analysis of the genomic DNA obtained revealed a low intraspecific polymorphism and did not allow for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
0
16
0
6
Order By: Relevance
“…RAPD-PCR was performed with total volume of 50 μl consisting of 10 μl of 50x master mix (Promiga, USA ) with 37 μl molecular-grade water, 0.5 μl template DNA and 1.5 μl (50 pmole) for each random primers RP1-4: TAGGATCAGA and SOY: AGGTCACTGA (Valerio et al, 2006). Amplified PCR conditions were as follows: 95°C for 4 min, 38 cycle 94°C for 1 min, 36°C for 1.5 min, 72°C for 1.5 min.…”
Section: Rapd-pcrmentioning
confidence: 99%
“…RAPD-PCR was performed with total volume of 50 μl consisting of 10 μl of 50x master mix (Promiga, USA ) with 37 μl molecular-grade water, 0.5 μl template DNA and 1.5 μl (50 pmole) for each random primers RP1-4: TAGGATCAGA and SOY: AGGTCACTGA (Valerio et al, 2006). Amplified PCR conditions were as follows: 95°C for 4 min, 38 cycle 94°C for 1 min, 36°C for 1.5 min, 72°C for 1.5 min.…”
Section: Rapd-pcrmentioning
confidence: 99%
“…It is easy and rapid but presents reproducibility problems inter and intra laboratories (107). There are reports about its application for several Candida species (86,116). Recently, two new techniques arouse: amplified fragment length polymorphism (AFLP) (3) and multilocus sequence typing (MLST) (12,32,115).…”
Section: Molecular Biologymentioning
confidence: 99%
“…Apart from corroborating previous studies that reported failure of microbiological techniques to identify Candida species 1 22 , the present study has successfully identified Candida isolates. It was able to discriminate between species through the use of a single primer, while other studies have reported success in Candida species typing through the use of a set of primers 24 . We conclude that RAPD with the primer OP-G10 could be performed after culture isolation, in order to confirm microbiological species identification, thus providing faster and more reliable Candida species typing.…”
Section: Discussionmentioning
confidence: 97%